LEGAL PROTECTION OF THE MEDICAL PROFESSION IN THE EXERCISE OF MEDICAL ACTIVITIES FROM A CRIMINAL LAW PERSPECTIVE - Taufan Nugroho; Thamrin. S; Abdul Thalib (Proceeding International Conference on Social Sciences, 2026)
The medical profession carries a significant responsibility in providing healthcare services to the public. However, in practice, doctors frequently encounter legal challenges, including accusations of medical crimes that can arise from their medical procedures. Therefore, legal protection is essential for doctors to carry out their professional duties safely and without worry. Problem Formulation: First, how is the implementation of legal protection for the medical profession according to the provisions of laws and regulations in Indonesia? Second, what are the forms of obstacles faced in efforts to provide legal protection to doctors when performing medical procedures? Research Objectives: First, to identify, study, and analyze the implementation of legal protection for the medical profession based on Indonesian laws and regulations. Second, to identify, study, and analyze obstacles to the implementation of legal protection for the medical profession in performing medical procedures. Research method: The researcher uses a normative juridical method, and to complement this research, the researcher uses an empirical/sociological method as an addition. Conclusion: First. There are many regulations related to the protection of the medical profession in carrying out medical procedures, such as: Article 27 of Law Number 36 of 2009 concerning Health, Article 24 of Government Regulation Number 32 of 1996 concerning Health Workers, Article 4 of Law Number 36 of 2014 concerning Health, Article 50 of Law Number 29 of 2004 concerning Medical Practice, Article 57 of Law Number 36 of 2014 concerning Health Workers. The results prove that all of these regulations do not support each other, but rather overlap and cannot be used as a strong guarantee for the medical profession. Second, the obstacles created, such as statements from police officers, prosecutors, professional organizations and others, apparently do not solve the problem of protecting the medical profession in seeking justice for the medical profession, because of the egos of each of them.